ANALISIS PERANAN KOMUNIKASI KELOMPOK GAMER’S ONLINE MOBILE LEGENDS PADA SKUAD X-COA DI KELURAHAN UJUNA KOTA PALU - Sasmita, Hadi Djaya (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2020)
This research aims to find out the role of online mobile legends gamer's group communication in the X-coa squad in Ujuna Village, Palu City. This research uses the Beal, Bohlen, and Raudabaugh model of the role of group members, namely group tasks, group maintenance and individual. The informants in this study were 3 people consisting of the squad leader, active squad members and members who had left the squad using a purposive sampling technique, namely determining the criteria determined by the researcher. The data analysis technique in this research uses qualitative data analysis techniques. Using observation, interviews and documentation methods. The results of this research show that the role of mobile legends online game group communication in the X-coa squad occurs while playing games and outside of playing games. In the role of group communication when playing games, open communication occurs. Supported by voice conversation features and instant messages, members are free to communicate the messages they want to convey. However, the message delivery feature provided does not make the communication climate warm when playing games. This is because conflicts often arise due to gamers' behavior, such as playing uncoordinatedly, not providing enough information when there is a lag, not following established rules, the lack of a leader's role in providing understanding about the use of terms in the game, which then triggers rude and impolite language when delivering message. Outside of playing games, the role of squad leader is quite good with the use of communication media in the form of WhatsApp to maintain relationships between fellow members. However, this squad also did not avoid problems because the essence of the conversation that was built in the group was mutually criticizing and inciting each other. Apart from that, problems when playing games are often carried over into their conversations when they are not playing games because there is no resolution provided when conflicts arise between players in the X-coa squad.